Business globalization process and its impact on Serbia's economic system - Vesić Dobrica (Međunarodni Problemi)
The changes companies are facing at the beginning of this century result from the impact of three factors. The first factor is globalization - a huge increase in exchange and availability of new products and services and a dramatic increase in mobility of foreign investment, movement of people and international competition. Another factor is the impact of modern communications technology. Rapid changes in all forms of technology allow a rapid access to various ways of communication with low cost, what leads to opening of markets to consumers worldwide. These two factors have contributed to the change of power in the market from producers to consumers or end users. Within this context, the availability of information in the company as well as the determination of global brands and services becomes a phenomenon of global markets.